Agresivitas Pajak di Pertambangan Batu Bara: Peran Capital Intensity dan Inventory Intensity di BEI - Fahlevie, Recja; Anggraini, Leriza Desitama; Meiriasari, Vhika (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
Low tax compliance among companies remains a critical issue, encouraging the emergence of tax aggressiveness practices, particularly in the coal mining sector which is considered high-risk in terms of tax management. Previous studies have shown mixed results regarding the factors that affect the tax aggressiveness, such as capital intensity and inventory intensity, indicating a research gap. This study aims to examine the effect of capital intensity, inventory intensity, audit committee, and firm size towards tax aggressiveness in coal mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This study uses a quantitative method with purposive sampling of 10 companies, resulting in 19 data samples. Data were analyzed using panel data regression with the help of EViews 13 software. The result shows that capital intensity and inventory intensity have a significant effect towards tax aggressiveness, while the audit committee and firm size do not. This finding implies that companies and regulators should pay greater attention to asset management and inventory planning in designing effective tax strategies. Moreover, this study can serve as a reference for future study to explore other variables that may affect tax aggressiveness behavior more comprehensively.